Expanding the role of non-physician medical staff in primary care in Germany: protocol for a mixed-methods study exploring the perspectives of physicians in rural practices. Issue 7 (26th July 2022) - Averbeck, Heiner; Litaker, David; Fischer, Joachim E
Abstract : Introduction: Primary care faces substantial challenges worldwide through an increasing mismatch in supply and demand, particularly in rural areas. One option to address this mismatch might be increasing efficiency by delegation of tasks to non-physician medical staff. Possible influencing factors, motives and beliefs regarding delegation to non-physician medical staff and the potential of an expanded role, as perceived by primary care physicians, however, remain unclear. The aim of this study is to assess these factors to guide development of potential interventions for expanding the role of non-physician medical staff in delivering primary care services in rural Germany. Methods and analysis: This mixed-methods study based on the theoretical domains framework (TDF) consists of survey and interviews conducted sequentially. The survey, to be sent to all primary care physicians active in rural Baden-Wuerttemberg (estimated n=1250), includes 37 items: 15 assessing personal and practice characteristics, 15 matching TDF domains and 7 assessing opportunities for delegation. The interview, to be performed in a subsample (estimated n=12–20), will be informed by results of the survey. The initial interview guide consists of 11 questions covering additional TDF domains. Perspectives towards delegation will be maximised by comparing data emerging in either part of the study, seeking confirmation, disagreement or further details. Ethics and dissemination: The Ethics Committee of Heidelberg University approved this study (approval number: 2021–530). Written informed consent will be obtained before each interview; consent for participation in the survey will be assumed when the survey has been returned. Results will be disseminated via publications in peer-reviewed journals and talks at conferences. By combining quantitative and qualitative methods, our results will support future research for crafting potential interventions to expand the role of non-physician medical staff in rural primary care.